A theoretical model for calculating the effects of carrier heating with nonequilibrium hot phonons on semiconductor devices and the current-voltage relations. (December 2018) - Tsai, Chin-Yi
Abstract: A theoretical model is proposed and presented to calculate carrier heating with nonequilibrium hot-phonon effects on semiconductor devices. The effects of nonequilibrium hot phonons are incorporated in the calculation of the intraband energy relaxation rates of the interactions between carriers and polar longitudinal optical (LO) phonons. This model and its rate equations of carrier number and energy densities are employed for the numerical calculation of the magnitude of carrier heating and its effects on the current-voltage relation of semiconductor devices. Simulation results show that the effects of carrier heating significantly make the current-voltage relation deviate from the exponential form of an ideal diode and the output current saturate at high applied voltages. Carrier temperatures are shown to reach several thousand degrees for devices with small active regions. The results suggest that carrier heating will become more severe and noticeable for semiconductor devices with active regions of nano-size structures. The results conclude that the methods of using the classical Maxwell-Boltzmann distribution function for carriers with a single energy relaxation time or theoretical models without hot-phonon effects are both inadequate and questionable for studying carrier heating problems. Highlights: A theoretical model is proposed to calculate carrier heating in semiconductor devices and the current-voltage relation. Intraband carrier energy relaxation rates are calculated with the effects of nonequilibrium hot phonons. Theoretical models without nonequilibrium hot-phonon effects are inadequate for studying carrier heating problems.